Group Analysis and Quantum Ontology: A Study of the Theoretical and Clinical Applications of Quantum Mechanics in the Group-Analytic Group - Anastassios Koukis (Forum for Group Psychotherapies and Processes)
The scientific foundations of group analysis are explored by drawing analogies between the group analytic process and quantum ontology. The group-analytic situation is conceived as a wave function process leading to collapses, according to Schrödinger’s equation and the interpretation of the Copenhagen School, through the conductor’s interpretative interventions. Superposition, as expressed by the conductor’s three positions (as therapist/member, father/mother and leader/conductor) and those of the members (adults/infants), as linked with mirror/resonance phenomena, are investigated. Heisenberg’s uncertainty principle is related to the impossibility of simultaneously “measuring” the conductor/father’s paternal position (Signifier/Name-of-the-Father) and his/ her dynamic influence (“speed”) on the group/mother or Signified (the mother/ group’s desire) (Lacan). A reservation regarding the exact determination of the Signifier and/or Signified using the uncertainty principle leads to a balance of power between them, which favours the pre-eminence of the conductor/father as expressing an effective paternal function by recognizing the group/mother as the major therapeutic figure (Foulkes).